Instagram® and Facebook® as platforms for the construction of social cartographies in the university classroom - Vargas Pérez, Manuel Alberto (2025)
This study explores the use of Instagram® and Facebook® as pedagogical tools for constructing social cartographies in Social Work and International Trade courses at the University of Tarapacá (Chile) and the Universidad Internacional de las Américas (Costa Rica). Employing a qualitative approach, focus groups conducted in 2018 and 2023 examined students’ perceptions and learning outcomes as they investigated social phenomena in their local contexts, influenced by personal and historical experiences. The findings indicate that these platforms, when purposefully integrated into educational settings, foster critical thinking, enhance social awareness, and strengthen the connection between theory and practice. Nevertheless, challenges emerged regarding subjective interpretations of content and varying levels of student engagement. The study concludes that social media, when guided by clear pedagogical frameworks, can serve as valuable resources for advancing critical and participatory teaching practices in diverse educational environments.